A (s)word against Babylon: an examination of the multiple speech act layers within Jeremiah 50-51 - Holroyd, Kristofer D. (Siphrut, 2017)
"Recent scholarship has demonstrated the value of speech act theory for biblical studies; for example, the studies of Walter Houston, Jim Adams, and Steven Mann have established its worth for Old Testament studies, exploring the declarative power of the prophetic word and the formative power of self-involved readings of the text. Additionally, John Searle and Daniel Vanderveken note that illocutionary acts seldom occur alone but rather in larger speech acts. The biblical text is replete with these larger speech acts; the book of Jeremiah provides an excellent example of such complicated larger speech acts. How, then, are we to study these complex speech acts? How can understanding these complex speech acts better inform our understanding of a text and of how a larger text employs smaller text portions or smaller illocutions within that complex speech act? In this study, I propose that speech act theory can help us understand complex texts and begin to answer these questions. More specifically, I propose that a more complex use of speech act theory--a multilevel speech approach--can help us study complex speech acts, such as the text of Jeremiah, by identifying the multiple smaller speech acts which make up the more complex speech acts. Furthermore, such an approach informs the understanding of both the smaller and larger speech acts and how the larger, more complex speech act employs the smaller speech acts toward the formation of the more complex act. In order to test and demonstrate this multilevel speech act approach, I will apply it to the oracle against Babylon in MT Jer 50-51 and examine the illocutionary force of that oracle at some of its performative levels"--